The tabligh language of the millenial generation in social media: Analysis of popular Islamic account framing - Ridwan Rustandi (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This study aims to analyze the construction of tabligh language based on religious moderation in social media. The research was conducted by taking the research object of Popular Islamic accounts on three social media platforms, namely Facebook, YouTube, and Instagram. Specifically, the research is directed at studying expressive, conventional, rhetorical logic, and religious moderation tabligh language negotiations for the millennial generation. An interpretive paradigm was chosen in this study.Method - Qualitative approach through the Gamson and Modigliani model framing analysis method was chosen to analyze the packaging pattern of the tabligh language. Data were collected through observation, interview, and documentation techniques. Furthermore, it is analyzed through three stages: reduction, display, and verification.Result - The study results conclude that the expressive logic of the tabligh language contained in the Popular Islam account is related to the normativity and actuality of Islamic teachings. The conventional logic set by the Popular Islam account is based on normative arguments, actual arguments, opinions of Islamic leaders, metaphors or parables, and phenomena that are trending in society. Rhetorical logic is carried out by using language style, communication principles, appeals and message organizational structures, and visualizing messages in a way that links symbols, images, and text. The negotiation of religious moderation discourse is packaged by showing the face of Islam on two sides, namely the doctrinal side and the actual side. Popular Islam places historical, empirical, and actual religious reality as the core issue of Islamic ideas. Moderate and accurate packaging tools are presented both within the framework of framing and reasoning of Popular Islamic accounts.Implication – The implications of this research relate to the importance of building theological, technological, and humanist awareness in preparing the infrastructure and ecosystem of da'wah resources to face the era of digital industrialization.Originality - This study analyzes the phenomenon of how the choice of diction and tabligh language style regarding religious messages based on religious moderation is presented in a virtual space.***Tujuan - Penelitian ini bertujuan untuk menganalisis konstruksi bahasa tabligh berdasarkan moderasi beragama di media sosial. Penelitian dilakukan dengan mengambil objek penelitian akun Islami Populer di tiga platform media sosial yaitu Facebook, YouTube, dan Instagram. Secara spesifik, penelitian diarahkan untuk mengkaji negosiasi bahasa tabligh ekspresif, konvensional, logika retoris, dan moderasi agama bagi generasi milenial. Paradigma interpretif dipilih dalam penelitian ini.Metode - Pendekatan kualitatif melalui metode analisis framing model Gamson dan Modigliani dipilih untuk menganalisis pola pengemasan bahasa tabligh. Pengumpulan data dilakukan melalui teknik observasi, wawancara, dan dokumentasi. Selanjutnya dianalisis melalui tiga tahap yaitu reduksi, display, dan verifikasi.Hasil - Hasil penelitian menyimpulkan bahwa logika ekspresif bahasa tabligh yang terdapat dalam akun Islam Populer berkaitan dengan normativitas dan aktualitas ajaran Islam. Logika konvensional yang ditetapkan oleh akun Islam Populer didasarkan pada argumen normatif, argumen aktual, pendapat para pemimpin Islam, metafora atau perumpamaan, dan fenomena yang sedang tren di masyarakat. Logika retoris dilakukan dengan menggunakan gaya bahasa, prinsip komunikasi, daya tarik dan struktur organisasi pesan, dan memvisualisasikan pesan dengan cara menghubungkan simbol, gambar, dan teks. Negosiasi wacana moderasi keagamaan dikemas dengan menampilkan wajah Islam dalam dua sisi, yaitu sisi doktrinal dan sisi aktual. Islam kerakyatan menempatkan realitas keagamaan historis, empiris, dan aktual sebagai isu inti gagasan-gagasan Islam. Alat pengemasan yang moderat dan akurat disajikan baik dalam kerangka pembingkaian dan penalaran akun Islami Populer.Implikasi – Implikasi penelitian ini berkaitan dengan pentingnya membangun kesadaran teologis, teknologis, dan humanis dalam mempersiapkan infrastruktur dan ekosistem sumber daya dakwah untuk menghadapi era industrialisasi digital.Orisinalitas - Penelitian ini menganalisis fenomena bagaimana pilihan diksi dan gaya bahasa tabligh tentang pesan-pesan keagamaan berbasis moderasi keagamaan dihadirkan dalam ruang virtual.